Gangliocytoma associated with focal cortical dysplasia in a young-adult: A case report [Erişlkin bir olguda gangliositomla ilişlkili fokal kortikal diplazi: Olgu sunumu] - (:unkn) unknown (Turkish Neurosurgical Society, 2008)
Neoplasms and (non-neoplastic) focal dysplasias may coexist as a cause of seizures in both the developing and mature brain. Low grade neoplastic lesions (ganglioglioma/gangliocytoma) may present with seizures, and distinction of these lesions from focal cortial dysplasia is difficult on standard radiological imaging. We report a 24-year-old man who had complaints of tonic-clonic seizures for one week duration and was admitted to department of neurosurgery. He did not have any neurological deficit on his examination. Cranial computerized tomography and magnetic resonance imaging of the patient revealed a calcified, cystic lesion with contrast enhancement, in the left temporoparietal region. Subtotal resection of the mass was performed. Pathological examination revealed focal cortical dysplasia associated with gangliocytoma.
Keywords: Calcified tumor; Focal cortical dysplasia; Gangliocytoma; Ganglioglioma